Restorative proctocolectomy impairs fertility and pregnancy outcomes in women with ulcerative colitis. (30th July 2013) - Tulchinsky, H.; Averboukh, F.; Horowitz, N.; Rabau, M.; Klausner, J. M.; Halpern, Z.; Dotan, I.
Abstract Aim The effect of restorative proctocolectomy (RPC) on fertility and pregnancy in women with ulcerative colitis (UC) was evaluated. Method Post‐RPC female patients with UC who were attempting to become pregnant filled out questionnaires on fertility and pregnancy. Demographic and pouch data of pregnancies ending with delivery were collected from a prospective database. Results Forty‐one women, 44 ± 10 years of age, completed the questionnaires. The median follow‐up period post‐RPC was 167 (range, 20–352) months. Before RPC, 26 women had 70 pregnancies and 62 deliveries. After RPC, 17 women had 32 pregnancies and 26 deliveries (P = 0.0035). Post‐RPC, 10 (37%) of 27 patients failed to conceive compared with 26/26 successful attempts before RPC (P = 0.0006). The number of offspring per patient was 2.38 ± 1.27 before, and 0.68 ± 0.93 after, RPC (P < 0.0001). A higher number of spontaneous pregnancies occurred before (56/62; 90%) than after (15/25; 60%) RPC (P = 0.0004). The time to conception was longer (5.0 ± 11.6 vs 16.3 ± 25.1 months; P = 0.039) and there were more in‐vitro fertilization procedures (three vs six) post‐RPC. The gestation period was similar, but after RPC more deliveries were by Caesarean section (12.9% vs 46.2%; P = 0.0007). Babies born before RPC weighed more than those born after RPC (3.16 ± 0.61 kg vs 2.79 ± 0.68 kg, respectively; P = 0.0327). Conclusion RPC is associated with an increased risk of infertility, similar duration of gestation and lower birthweight. Female candidates for RPC who have not finished family planning should be counselled accordingly.